Pengaruh Disiplin Kerja dan Komunikasi terhadap Prestasi Kerja : Survei pada Karyawan Bagian Pemasaran PT. Bumi Makmur Indah Pangandaran - Sinta Anisa Riswanda; Arga Sutrisna; Barin Barlian (CV. Ulil Albab Corp, 2022)
This study aims to determine the effect of work discipline and communication on work performance (a survey of employees in the marketing division of PT. Bumi Makmur Indah Pangandaran). This type of research is quantitative research with causality method and survey approach. The sample that will be selected in this study is the Marketing Section Employees of PT. Bumi Makmur Indah Pangandaran as many as 27 people. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that work discipline and communication had a significant influence on job performance for employees of the marketing division of PT. Beautiful Prosperous Earth in Pangandaran. Partially, Work Discipline has not a significant influence on Work Performance for Employees in the Marketing Division of PT. Beautiful Prosperous Earth in Pangandaran. Communication has a significant influence on the work performance of employees in the marketing division of PT. Beautiful Prosperous Earth in Pangandaran.